"...and then she died" : Indonesia Maternal Health Assessment - World Bank (World Bank, 2012)
Maternal health remains one of the top priorities of the Government of Indonesia (GoI) and the Ministry of Health (MoH) because reductions in maternal mortality have been slows. The current Maternal Mortality Ratio (MMR) for Indonesia is 228 but with existing programs and interventions the government does not believe it will be able to achieve its stated millennium development goal of 102 maternal deaths per 100,000 live births by 2015. There are positive trends in an increased use of skilled birth attendants, almost universal access to some level of antenatal care and continued use of family planning but these are not enough to stem the tide of maternal death. Interventions by the skilled birth attendants in many cases are not in line with existing standards and prove to be ineffective in trying to address the emergence of complications. Antenatal care is important, but it is not where gains in decreased mortality will be obtained. The continued use of traditional birth attendants (TBA) and delivering at home are contributory factors to maternal mortality in Indonesia. In collecting data from verbal autopsies in three districts, (a widely used government initiative to determine the causes of maternal death) 63 out of 76 deaths occurred in home births that had been assisted by a TBA. In order to improve the access of the poor and the near poor to health services, the government is implementing the social insurance scheme, Jamkesmas. Approximately 104 million people should qualify for assistance but there are presently only 76.4 million people covered by this social health insurance (SHI) plan. Even those who are covered are not always able to afford care because of external expenses such as transportation charges which must be paid up front.